Their Road to the Buffalo - Ron Parks (Symphony in the Flint Hills, 2009)
A few miles north and east of the symphony site the well, timbered valleys of the Cottonwood River and Middle and Diamond creeks provided good winter camping sites for the Kanza (or Kaw) Indians. In January and February, 1860, hundreds of Kanzas were encamped in these valleys, the women engaged in the work of tanning and dressing buffalo robes brought in from their autumn and winter hunt on the plains.
Keywords: Kaw; Kanza; Kansas; Native Americans; Indians; people; tobacco; wool blankets; hunting; winter; Cottonwood River; life; work; tribe; journey; hunt; trade; animals; Bison; Buffalo jerk; Cheyenne tribe; ammunition; cotton cloth